Does the use of hernia mesh in surgical inguinal hernia repairs cause male infertility? A systematic review and descriptive analysis - Zhiyong Dong; Stacy Ann Kujawa; Cunchuan Wang; Hong Zhao (BMC, 2018)
Abstract Objective The aim of this study was to systematically review the available clinical trials examining male infertility after inguinal hernias were repaired using mesh procedures. Methods The Cochrane Library, PubMed, Embase, Web of Science, and Chinese Biomedical Medicine Database were investigated. The Jada score was used to evaluate the quality of the studies, "Oxford Centre for Evidence-based Medicine-Levels of Evidence" was used to assess the level of the trials, and descriptive analysis was used to evaluate the studies. Results Twenty nine related trials with a total of 36,552 patients were investigated, including seven randomized controlled trials (RCTs) with 616 patients and 10 clinical trials (1230 patients) with mesh or non-mesh repairs. The Jada score showed that there were six high quality RCTs and one low quality RCT. Levels of evidence determined from the Oxford Centre for Evidence-based Medicine further demonstrated that those six high quality RCTs also had high levels of evidence. It was found that serum testosterone, LH, and FSH levels declined in the laparoscopic group compared to the open group; however, the testicular volume only slightly increased without statistical significance. Testicular and sexual functions remained unchanged after both laparoscopic transabdominal preperitoneal hernia repair (TAPP) and totally extra-peritoneal repair (TEP). We also compared the different meshes used post-surgeries. VyproII/Timesh lightweight mesh had a diminished effect on sperm motility compared to Marlex heavyweight mesh after a one-year follow-up, but there was no effect after 3 years. Additionally, various open hernia repair procedures (Lichtenstein, mesh plug method, posterior pre-peritoneal mesh repair, and anterior tension-free repair) did not cause infertility. Conclusions This systematic review suggests that hernia repair with mesh either in an open or a laparoscopic procedure has no significant effect on male fertility.